2018
DOI: 10.3171/2017.6.spine17282
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of predictive factors of vertebral compression fracture after conventional palliative radiotherapy for spinal metastasis from colorectal cancer

Abstract: OBJECTIVEDelayed consequences of spinal radiotherapy (RT), including vertebral compression fracture (VCF), are critical complications. However, the predisposing factors that contribute to VCF after conventional RT are unclear. The aim of this study was to assess the incidence of VCF and to determine the predictors of VCF following conventional spinal RT specific to colorectal cancer (CRC).METHODSThe author… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 27 publications
0
15
1
Order By: Relevance
“…Surgical treatment has been applied extensively in spinal metastasis. It was reported 21 that direct decompressive surgery combined with local radiotherapy could achieve better functional preservation compared with radiotherapy alone. It has been reported that separation surgery followed by postoperative radiotherapy were recommended for the treatment of patients with spinal metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical treatment has been applied extensively in spinal metastasis. It was reported 21 that direct decompressive surgery combined with local radiotherapy could achieve better functional preservation compared with radiotherapy alone. It has been reported that separation surgery followed by postoperative radiotherapy were recommended for the treatment of patients with spinal metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…reported the occurrence of new VBC as 9% in colorectal cancer 13 . But the investigation of occurrence of VBC in these studies limited to all patient.…”
Section: Discussionmentioning
confidence: 98%
“…The conventional RT is the most common treatment for spinal SREs. However, the rate of occurrence and progression of new VBC after RT has not been fully investigated 12,13 . Furthermore, to the best of our knowledge, no studies have focused on the evaluation of time course of spinal instability after RT and potential risk factors for differences in spinal instability in patients with painful vertebral bone metastases without paralysis by MSCC by SINS.…”
Section: Introductionmentioning
confidence: 99%
“…Among 13 studies, 11 studies agreed that the categories of the SINS described statistical significance in predicting VCFs. Eight studies reported accuracy of each item of the SINS 3,5,6,12,19,28,29,33) . Six studies agreed that body collapse was effective in predicting VCFs.…”
Section: Accuracy Of Sins To Predict Vcfmentioning
confidence: 99%